2021
DOI: 10.1139/cjfas-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

The response of a brown trout (Salmo trutta) population to reintroduced Eurasian beaver (Castor fiber) habitat modification

Abstract: Globally, freshwaters are the most degraded and threatened of all ecosystems. In northern temperate regions, beaver (Castor spp.) reintroductions are increasingly used as a low-cost and self-sustaining means to restore river corridors. River modifications by beavers can increase availability of suitable habitat for fish, including salmonids. This study investigated the response of a population of brown trout (Salmo trutta) to reintroduced Eurasian beaver (Castor fiber) habitat modifications in northern Scotlan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…These effects were observed on the scale of individual habitats within streams (Hägglund & Sjöberg, 1999; Malison & Halley, 2020). Conversely, when the abundance of S. trutta was examined at the stream scale by Needham et al (2021), abundance in a beaver‐altered stream was equal to or higher than abundance in an unaltered stream. Bylak, Kukula & Mitka (2014) observed that mature S. trutta frequently inhabited beaver ponds in Poland and used upstream habitats for spawning.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were observed on the scale of individual habitats within streams (Hägglund & Sjöberg, 1999; Malison & Halley, 2020). Conversely, when the abundance of S. trutta was examined at the stream scale by Needham et al (2021), abundance in a beaver‐altered stream was equal to or higher than abundance in an unaltered stream. Bylak, Kukula & Mitka (2014) observed that mature S. trutta frequently inhabited beaver ponds in Poland and used upstream habitats for spawning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there are diverse opinions regarding beaver impacts upon fish (Auster, Barr, & Brazier, 2020a). Research here continues, although existing literature suggests varied but net beneficial effects (Bouwes et al, 2016;Brazier, Puttock, et al, 2020;Bylak & Kukuła, 2018;Kemp, Worthington, Langford, Tree, & Gaywood, 2012;Malison & Halley, 2020;Needham et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, there are diverse opinions regarding beaver impacts upon fish (Auster, Barr, & Brazier, 2020a). Research here continues, although existing literature suggests varied but net beneficial effects (Bouwes et al, 2016;Brazier, Puttock, et al, 2020;Bylak & Kukuła, 2018;Kemp, Worthington, Langford, Tree, & Gaywood, 2012;Malison & Halley, 2020;Needham et al, 2021).…”
Section: Introductionmentioning
confidence: 97%